2019
DOI: 10.1007/s10570-018-2202-8
|View full text |Cite
|
Sign up to set email alerts
|

Arabinose substitution effect on xylan rigidity and self-aggregation

Abstract: Substituted xylans play an important role in the structure and mechanics of the primary cell wall of plants. Arabinoxylans (AX) consist of a xylose backbone substituted with arabinose, while Glucuronoarabinoxylans (GAX) also contain glucuronic acid substitutions and ferulic acid esters on some of the arabinoses. We provide a molecular-level description on the dependence of xylan conformational, self-aggregation properties and binding to cellulose on the degree of arabinose substitution. Molecular dynamics simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 58 publications
(70 reference statements)
0
22
0
Order By: Relevance
“…The side groups of xylan are known to prevent the intermolecular aggregation, which happens for a linear molecule such as cellulose that tends to crystallize. The side groups would thus greatly affect the properties of xylan (Dea et al, 1973;Hoije et al, 2008;Shrestha et al, 2019). The solubility of xylan in water decreased with decreasing number of side groups as the unsubstituted segments would aggregate into insoluble form (Andrewartha et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The side groups of xylan are known to prevent the intermolecular aggregation, which happens for a linear molecule such as cellulose that tends to crystallize. The side groups would thus greatly affect the properties of xylan (Dea et al, 1973;Hoije et al, 2008;Shrestha et al, 2019). The solubility of xylan in water decreased with decreasing number of side groups as the unsubstituted segments would aggregate into insoluble form (Andrewartha et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Xylan is generally known as an amorphous polymer. However, with reduced number of side groups, xylan can form hydrous and anhydrous crystals (Dea et al, 1973;Hoije et al, 2008;Horio and Imamura, 1964;Kobayashi et al, 2013;Marchessault and Timell, 1960;Nieduszynski and Marchessault, 1972), which greatly hinders the polymer internal rotation and thus increase the rigidity (Arinstein et al, 2007;De Rosa et al, 2006;Fama et al, 2005;Shrestha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Simple theories established for semiflexible homopolymers and heteropolymers have been shown to provide a qualitative description of IDP structural properties such as stiffness 67 69 and solvent quality 12 , 14 , 55 , 70 , 71 . The high fidelity HREMD trajectories reveal that, despite having markedly different sequences, the IDPs studied here have common hierarchical chain architecture.…”
Section: Discussionmentioning
confidence: 99%
“…However, substitutions at the α-(1→2) position are low in miscanthus, as the amount of α-(1→3)-linked arabinosyl units is between 4 and 6 times higher compared to the amount positioned at the α-(1, →2) position in stems [ 128 ]. Results from another simulation study reported stronger binding of less substituted arabinoxylan to cellulose, but also showed strong binding of ferulic acid to cellulose, proposing that ferulic acid could play an important role in arabinoxylan to cellulose interactions [ 147 ]. Clearly, further research would be needed to confirm if such interactions occur in vivo in the cell walls of miscanthus.…”
Section: Cell Wall Composition In Relation To Cell Wall Digestibilmentioning
confidence: 99%